h - Lee, Kyoung Mu.; Matsushita, Yasuyuki; Rehg, James M.; Hu, Zhanyi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The four-volume set LNCS 7724--7727 constitutes the thoroughly refereed post-conference proceedings of the 11th Asian Conference on Computer Vision, ACCV 2012, held in Daejeon, Korea, in November 2012. The total of 226 contributions presented in these volumes was carefully reviewed and selected from 869 submissions. The papers are organized in topical sections on object detection, learning and matching; object recognition; feature, representation, and recognition; segmentation, grouping, and classification; image representation; image and video retrieval and medical image analysis; face and gesture analysis and recognition; optical flow and tracking; motion, tracking, and computational photography; video analysis and action recognition; shape reconstruction and optimization; shape from X and photometry; applications of computer vision; low-level vision and applications of computer vision.
Oral Session 8: Shape Reconstruction and Optimization -- Self-calibration and Motion Recovery from Silhouettes with Two Mirrors -- Stereo Reconstruction and Contrast Restoration in Daytime Fog -- Large-Scale Bundle Adjustment by Parameter Vector Partition -- Learning Feature Subspaces for Appearance-Based Bundle Adjustment -- Poster Session 8: Shape from X and Photometry -- Toward Efficient Acquisition of BRDFs with Fewer Samples -- Sato Shadow-Free TILT for Facade Rectification -- Reconstructing Shape from Dictionaries of Shading Primitives -- Iterative Feedback Estimation of Depth and Radiance from Defocused Images -- Two-Image Perspective Photometric Stereo Using Shape-from-Shading -- Stable Two View Reconstruction Using the Six-Point Algorithm -- Unknown Radial Distortion Centers in Multiple View Geometry Problems -- Depth-Estimation-Free Condition for Projective Factorization and Its Application to 3D Reconstruction -- Epipolar Geometry Estimation for Urban Scenes with Repetitive Structures -- Non-rigid Self-calibration of a Projective Camera -- Piecewise Planar Scene Reconstruction and Optimization for Multi-view Stereo -- A Bayesian Approach to Uncertainty-Based Depth Map Super Resolution -- Cross Image Inference Scheme for Stereo Matching -- Bayesian Epipolar Geometry Estimation from Tomographic Projections -- On the Global Self-calibration of Central Cameras Using Two Infinitesimal Rotations -- Adaptive Structure from Motion with a Contrario Model Estimation -- Precise 3D Reconstruction from a Single Image -- An Efficient Image Matching Method for Multi-View Stereo -- Self-calibration of a PTZ Camera Using New LMI Constraints -- Fast 3D Surface Reconstruction from Point Clouds Using Graph-Based Fronts Propagation -- Oral Session 9: Applications of Computer Vision Apparel Classification with Style -- Deblurring Vein Images and Removing Skin Wrinkle Patterns by Using Tri-band Illumination -- Reconstruction of 3D Surface and Restoration of Flat Document Image from Monocular Image Sequence -- Utilizing Optical Aberrations for Extended-Depth-of-Field Panoramas -- Poster Session 9: Low-level Vision and Applications of Computer Vision -- Motion-Invariant Coding Using a Programmable Aperture Camera -- Color-Aware Regularization for Gradient Domain Image Manipulation -- Local Covariance Filtering for Color Images -- A New Projection Space for Separation of Specular-Diffuse Reflection Components in Color Images -- Hand Vein Recognition Based on Oriented Gradient Maps and Local Feature Matching -- Fusing Warping, Cropping, and Scaling for Optimal Image Thumbnail Generation -- Shift-Map Based Stereo Image Retargeting with Disparity Adjustment -- Object Templates for Visual Place Categorization -- Reconstructing Sequential Patterns without Knowing Image Correspondences -- Registration of Multi-view Images of Planar Surfaces -- Automatic Stave Discovery for Musical Facsimiles -- Unsupervised Language Learning for Discovered Visual Concepts -- Parameterized Variety Based View Synthesis Scheme for Multi-view 3DTV -- Quasi-regular Facade Structure Extraction -- Multi-view Synthesis Based on Single View Reference Layer -- Hand-Eye Calibration without Hand Orientation Measurement Using Minimal Solution -- Detecting Changes in Images of Street Scenes -- Adaptive Background Defogging with Foreground Decremental Preconditioned Conjugate Gradient -- A Shadow Repair Approach for Kinect Depth Maps -- A Unified Framework for Line Extraction in Dioptric and Catadioptric Cameras -- Fusion of Time-of-Flight and Stereo for Disambiguation of Depth Measurements.
Keywords: Computer science; Medical records -- Data processing; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Artificial Intelligence (incl. Robotics).; Health Informatics